Characterization of sugar metabolism in the stem of Tachisuzuka, a whole-crop silage rice cultivar with high sugar content in the stem. (3rd July 2018) - Hashida, Yoichi; Kadoya, Sakurako; Okamura, Masaki; Sugimura, Yu; Hirano, Tatsuya; Hirose, Tatsuro; Kondo, Satoshi; Ohto, Chikara; Ohsugi, Ryu; Aoki, Naohiro
Abstract: Tachisuzuka, a rice cultivar for whole-crop silage, is characterized by a small panicle and high sugar content in the stem. Our previous study suggests that the high sugar content in the stem of Tachisuzuka is due to a factor other than the small panicle. To characterize sugar metabolism in the stem of Tachisuzuka, here we compared carbohydrate content, enzyme activity, and the expression of genes involved in sugar metabolism in the stem between Tachisuzuka and its parental variety, Kusanohoshi. Thinning the panicles of Kusanohoshi increased the starch content in the leaf sheath and internode but did not increase the sucrose content in the leaf sheath to the same level as that of Tachisuzuka. This suggests that Tachisuzuka has high potential to accumulate sucrose in its leaf sheath. Comparison of enzyme activity showed that the hexokinase activities in the leaf sheath tended to be higher in Tachisuzuka than Kusanohoshi or panicle-thinned Kusanohoshi, suggesting that glucokinase or fructokinase affects sugar accumulation in the stem of Tachisuzuka. Comparative transcriptome analysis revealed the differences in expression levels of carbohydrate-related genes between Tachisuzuka and Kusanohoshi. In particular, the expression levels of ISA2, which encodes starch-debranching enzyme, and TMT2, which encodes tonoplast monosaccharide transporter – both of which maybe involved in sugar accumulation in grass stems – were higher in Tachisuzuka than Kusanohoshi. Thus, these enzymes and transporters may contribute to the high sugar content in the stem of Tachisuzuka.